(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2025)
This study was conducted to determine the financial reports preparation process and the impact of Accounting digitalization on the MSMEs studied. The research method used in this study is qualitative. The types of data taken are primary data and secondary data. Primary data were obtained by researchers through interviews and observations, while secondary data were obtained through the documentation process. Interviews were conducted with 3 key informants, namely the owner, the head of finance, and the cashier. The results of the study show that Pelangi Mart MSMEs have been preparing financial reports using the Accurate application. The Head of Finance carries out the preparation process. The impact of digitalization on the Accounting process for MSMEs is that it can increase the efficiency, accuracy, and quality of financial reports. In addition, digitalization can reduce costs related to HR management.